Resisting a postcolonial construction of historical trauma and healing: Critical discourse analysis of public apologies in Canada - Lee, Eunjung; Johnstone, Marjorie (Critical sociology, 2022)
The contemporary discourse around historical trauma and healing is site for debate and resistance in public spheres. Guided by critical scholars in language and power as well as post-and settler colonialism, this study analyzes texts and contexts of two public apologies in Canada – Chinese head tax, and residential schools for Indigenous children – to examine how historical trauma and healing were understood, and by doing so how the subject and object were re/constructed to maintain or resist social (dis)orders – postcolonial racial orders – in the past and the present of Canada. Findings included: (1) a split and temporal distance between the wrong past and the benevolent present with governments constructing themselves as the good subject reifying a sincere fiction of a liberal, benevolent, and just white-nation; (2) no acknowledgement of the cause of historical trauma, namely colonial governing; (3) ongoing construction of the other racialized population as victims/burdens/lesser citizens to current Canada; and (4) the explicit demand to collective forgetting of the past/historical trauma as current healing and inclusion. We discuss social responsibilities when historical wounds continue to leave injuries and the risk of perpetuating systemic violence to people with whom we currently share the nation all of us call home.